2014
DOI: 10.2340/00015555-1870
|View full text |Cite
|
Sign up to set email alerts
|

A New Ten-Item Questionnaire For Assessing Sensitive Skin: The Sensitive Scale-10

Abstract: Sensitive skin is common but until now there has been no scale for measuring its severity. The Sensitive Scale is a new scale with a 14-item and a 10-item version that was tested in 11 countries in different languages on 2,966 participants. The aim of this study was to validate the pertinence of using the Sensitive Scale to measure the severity of sensitive skin. The internal consistency was high. Correlations with the dry skin type, higher age, female gender, fair phototypes and Dermatology Life Quality Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 25 publications
4
109
0
1
Order By: Relevance
“…One previous study used the SF‐12, but did not show clear alterations and did not show effects on depressive symptomatology as ours did. Another study used DLQI and showed that a decrease in quality of life was associated with the severity of sensitivity assessed by the Sensitive Scale . This new study provides evidence of an impressive impact by sensitive skin on quality of life, and dermatologists should take these data in consideration.…”
Section: Discussionmentioning
confidence: 82%
“…One previous study used the SF‐12, but did not show clear alterations and did not show effects on depressive symptomatology as ours did. Another study used DLQI and showed that a decrease in quality of life was associated with the severity of sensitivity assessed by the Sensitive Scale . This new study provides evidence of an impressive impact by sensitive skin on quality of life, and dermatologists should take these data in consideration.…”
Section: Discussionmentioning
confidence: 82%
“…Sensitive skin can affect any part of the body, but it affects mainly the face (85%) and the hands (58%) . The diagnosis and evaluation of SSS can be performed in different ways, especially via a questionnaire, the Sensitive Scale . The Sensitive Scale is a good tool to assess SSS and is noninvasive.…”
mentioning
confidence: 99%
“…The Dermatology Life Quality Index (DLQI) is a very well‐known health quality‐of‐life scale specific for dermatological disorders . The Sensitive Scale evaluates nine symptoms of sensitive skin – eight subjective (tingling, burning, sensation of heat, tightness, itching, pain, general discomfort, flushes) and one objective (redness). Patients were asked to quantify each symptom from 1 to 10 on a numerical scale.…”
mentioning
confidence: 99%